Detection of a familial 21q22.3 microduplication in a fetus associated with congenital heart defects - Chih-Ping Chen; Chen-Yu Chen; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Tzu-Yun Chuang; Wayseen Wang (Elsevier, 2019)
Objective: We present a familial 21q22.3 microduplication in a fetus associated with prenatally detected congenital heart defects (CHD). Case report: A 38-year-old woman underwent amniocentesis at 22 weeks of gestation because of sonographic findings of double outlet of right ventricle, ventricular septal defect and transposition of great artery in the fetus. Her husband was 42 years old, and there was no CHD and congenital malformation in the family. Cytogenetic analysis revealed a karyotype of 46,XY in the fetus. Simultaneous array comparative genomic hybridization (aCGH) analysis using uncultured amniocytes revealed a 0.56-Mb microduplication of 21q22.3 or arr 21q22.3 (47,482,210-48,043,704)×3.0 [GRCh37 (hg19)] encompassing nine Online Mendelian Inheritance in Man (OMIM) genes of FTCD, SPATC1L, LSS, MCM3AP, YBEY, PCNT, DIP2A, S100B and PRMT2. aCGH analysis of the parental bloods revealed that the phenotypically normal father carried the same microduplication. The parents decided to continue the pregnancy, and a 3168-g male baby was delivered at term without Down syndrome phenotype except CHD. Mutational analysis of the CRELD1 gene on the DNA extracted from the cord blood showed no mutation in CRELD1. Postnatal molecular cytogenetic analysis of the cord blood confirmed the prenatal diagnosis. The infant underwent a successful heart surgery to correct the CHD and was doing well without psychomotor or developmental delay at six months of age. Conclusion: Prenatal diagnosis of 21q22.3 microduplication associated with CHD should include a differential diagnosis of Down syndrome. Keywords: 21q22.3 microduplication, Congenital heart defects, Prenatal diagnosis